2000
DOI: 10.1152/ajpregu.2000.278.2.r504
|View full text |Cite
|
Sign up to set email alerts
|

Lower calorie intake enhances muscle insulin action and reduces hexosamine levels

Abstract: Previous studies have demonstrated enhanced insulin sensitivity in calorie-restricted [CR, fed 60% ad libitum (AL) one time daily] compared with AL-fed rats. To evaluate the effects of reduced food intake, independent of temporal differences in consumption, we studied AL (unlimited food access)-fed and CR (fed one time daily) rats along with groups temporally matched for feeding [fed 3 meals (M) daily]: MAL and MCR, eating 100 and 60% of AL intake, respectively. Insulin-stimulated glucose transport by isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 46 publications
5
27
1
1
Order By: Relevance
“…The reduction in body weight, especially in adiposity, is associated with improvement in glucose tolerance (19) and insulin action (3,5). In our study, this improvement of glucose tolerance was reflected both by a reduced area under the glucose curve during the IPGTT in the fasting groups compared to the non-fasting ones and by a reduced postprandial glycemia which reached values comparable to those recorded before the switch period i.e., before the development of diabetes.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The reduction in body weight, especially in adiposity, is associated with improvement in glucose tolerance (19) and insulin action (3,5). In our study, this improvement of glucose tolerance was reflected both by a reduced area under the glucose curve during the IPGTT in the fasting groups compared to the non-fasting ones and by a reduced postprandial glycemia which reached values comparable to those recorded before the switch period i.e., before the development of diabetes.…”
Section: Discussionsupporting
confidence: 62%
“…Chronic moderate reduction in energy intake results in the opposite effects, namely increased insulin sensitivity and improved glucose homeostasis (1)(2)(3). In fact, caloric restriction is considered as a common treatment for obesity, insulin resistance and type 2 diabetes (4).…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with a previous study (16), muscle TG content was not significantly affected by short-term FR. However, there was a trend (P ϭ 0.14-0.21) for muscle TG to be lower in FR animals that may not have reached significance due to the relatively low TG levels in both groups and the relatively short period of FR.…”
Section: Discussionsupporting
confidence: 93%
“…With regard to the hexosamine biosynthetic pathway, it has been demonstrated that caloric restriction leads to a reduction in the concentration of UDP-N-acetylhexosamines, namely UDP-N-acetylglucosamine and UDP-N-acetylgalactosamine, the end products of this biosynthetic pathway (Gazdag et al, 2000). Worth noting is the fact that a role for N-acetylglucosamine as a nutrient sensor and mediator of insulin resistance has been proposed (for review see Wells et al, 2003;Zachara and Hart, 2004).…”
Section: Discussionmentioning
confidence: 99%